From Policy to Practice: Analyzing the Implementation of the Complete Systematic Land Registration in Palu City, Central Sulawesi - Syariatudin Syariatudin; Daswati Daswati; Sitti Chaeriah Ahsan; Syahruddin Hattab; Mustainah Mustainah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The study investigates the implementation of the Complete Systematic Land Registration (Indonesia: Pendaftaran Tanah Sistematis Lengkap/PTSL) policy in Palu City, Central Sulawesi Province. The research is qualitative, utilizing purposive sampling to select five key informants. Data collection was conducted through observations, in-depth interviews, and document analysis. Data analysis followed the Miles and Huberman approach, involving data editing, verification, and drawing conclusions. The findings, framed within Van Meter and Van Horn's theoretical model, reveal six key dimensions of policy implementation: (1) Standards and Targets, with positive community response, particularly in land certification; (2) Resources, with adequate human resources but suboptimal financial support; (3) Inter-organizational Communication and Activity Strengthening, marked by effective collaboration among related institutions; (4) Characteristics of Implementing Agents, with National Land Office (Indonesia: Badan Pertanahan Nasional (BPN) Palu City as the technical executing body; (5) Socio-Economic and Political Conditions, reflecting supportive social environments but financial constraints and regulatory challenges; and (6) Implementor Disposition, highlighting the positive reception of PTSL, which contributes to the empowerment of local communities and suggests potential for future expansion in other regions.